BIOPSYCHOSOCIAL AND PSYCHIATRIC ASPECTS OF INFIDELITY - Goldner-Vukov, Mila (Srpski medicinski časopis Lekarske komore, 2026)
Introduction/Objective: Infidelity is a complex biopsychosocial phenomenon with significant implications at the individual, relational, and family levels. Although traditionally viewed within moral, cultural, or social frameworks, contemporary evidence highlights the interplay of biological, psychological, and social determinants in the etiology of this phenomenon. Infidelity has been associated with attachment disorders, impulsivity, neurobiological and hormonal influences, traumatic experiences, personality pathology, and addictive behaviors. Its consequences may include severe mental health issues and disruption of partner relations and family stability. The present study aims to analyze the biopsychosocial and psychiatric aspects of infidelity in intimate and family relationships, with particular emphasis on etiological factors, clinical manifestations, and consequences for mental health, partner relationships, and family dynamics. Material and methods: This is a narrative review of relevant national and international literature in psychiatry, clinical psychology, family therapy, evolutionary psychology, and neurobiology. The analysis included studies addressing genetic predispositions, hormonal and neurotransmitter mechanisms, attachment patterns, personality traits, sociocultural determinants, and psychiatric outcomes associated with infidelity. Results: Infidelity is a multifactorial phenomenon. Biological contributors include genetic variability, hormonal and neurotransmitter influences, and activation of dopaminergic reward pathways. Psychological factors include insecure attachment styles, sensation seeking, narcissistic and borderline personality traits, childhood trauma, and impaired impulse control. Social determinants encompass cultural norms, occupational environments, and contemporary relationship models. Consequences of infidelity may include depression, anxiety, post-traumatic stress disorder, suicidal ideation, domestic violence, substance abuse issues, as well as long-term impairment of trust and intimacy. Conclusion: Infidelity should not be regarded solely as a moral or social issue, but as a complex clinical and societal phenomenon with substantial implications for mental health, partnership, and family stability. A comprehensive understanding of its biopsychosocial mechanisms enables more effective psychiatric and psychotherapeutic interventions aimed at improving individual and partnership functioning through the development of self-awareness, responsibility, and resilience.